Consumption Culture of Electricity between Rationalization and Waste/ A Social-Field Study in Baghdad Governorate (Journal of the College of Education for Women, 2024)
The research aims to shed light on the consumer culture of electrical energy for the Iraqi individual and its significant impact on the electricity crisis in Iraq, as well as to shed light on the importance of rationalizing consumption of electrical energy and the repercussions of waste and extravagance as it is a negative phenomenon. Consumers must be educated and aware to avoid its harm to the individual and society. The study was based on an approach of Social survey: A field sample of 200 consumers was selected in Baghdad Governorate in the two regions (Al-Karkh and Al-Rusafa) using a random sampling method. After applying the form and analyzing the results, the study reached a number of results, the most important of which are: The participants’ answers indicated that the wasting style of human behavior is still dominant among people, with their percentage reaching (54.5%). More than two-thirds of the participants (68%) confirmed that the number of Amperes is not sufficient for the household’s needs, especially since the income of the Iraqi homeland does not help in increasing the number of Amperes and meeting its energy needs due to the high price of Amperes from the private generator. The vast majority of respondents (90%) confirmed that paying generator electricity fees affects the economic situation of the family. The results of the study indicate that (76.5%) of the participants suffer from respiratory diseases due to emissions from power plants or generators. The study also concluded with recommendations aimed at educating citizens on how to rationalize electrical energy and avoid waste and profusion.